The Outer Space Within the Inner World the Streets of Istanbul in the Photographs of Ara Guler - Eceoğlu, Arzu (My University, 2013)
As a 19th century invention, after a long and tough journey, the photography has completed its technical invention when the first still image has been captured. Since the Camera Obscuras, its birth, the photography has continued its “documenting humans through humans’ eyes” function and through involving not only the technique, but also the art and the meaning, it served the humankind as the most important witness, documenting our history and memories. As a documentarian and an art laborer, searching for this meaning, the most important name of the photography history of Turkey, Ara Guler is a man of action supporting this idea. As an opposition to lots of famous names, who call themselves as photography artists, Guler identifies himself as a “photo journalist”. As a modern documentarian and a great master, he had lots of contributions on advertising Turkish photography in the international arena. From the point of view of Guler, the event is important within the “moment” and as he has brought humans into prominence in his photographs, he has also captured the harmony between “Space and Light”. The aim of this declaration is to see the streets of Istanbul before the “urban transformation”, analyze them using semiotics and examine the streets of Istanbul through a photographers eyes in the means of space.
Keywords: Fotoğrafçılık; Uzay; Çözümlemek; İstanbul Sokakları; Güler, Ara, 1928-2018; Photography; Space; Analyze; Streets of Istanbul